PERAWATAN DIRI SEHARI-HARI PASIEN HEMODIALISA DI MURNI TEGUH MEMORIAL HOSPITAL - Ongku Bosar Hasibuan (Indonesian Trust Health Journal, 2018)
Chronic kidney desease is a malfunction of kidney so that cannot maintain its metabolism fluid and electolyte imbalance. Patients with chronic kidney desease can be treated with a therapy of kedney substitute with hemodialysis to maintain their life. Hemdialysis patients have problems to self-care deficit in which affects to their activity daily living’s doe to complication such as weakness, hypotension, pain, cramps and teh others. The objective of this research was to identify activity daily living,s of hemodialysis patinets in Murni Teguh Memorial Hospital. This research used of descrivtive researsch. The sample were 35 responden who had to be following hemodialysis therapy with accidental sampling. Activity daily living’s was analyzed by the frequency and descriftive test. The result of this reserach is mayority of responden had moderate for nutritional management is 13 person (37.10%), mayority had bad for mobilization/movement activity is 13 person (37.10%), mayority had moderate abd bad for housekeeping, mayority had good for resting activuty is 14 person (40%) and mayority had moderate for activity of responsiblity to medicationt is 17 person (48.60%). This study shows that hemodialysis patinets have get a self-care disorders. It is expected to health workers to developve anurse training for program for attention and give the intervention to patients who had self-care disorders to be improve ability for maintanance their activity daily livings. Abstrak Penyakit ginjal kronis merupakan suatu kelainan fungsi ginjal secara menahun, mengakibatkan ginjal tidak mampu untuk mempertahankan metabolisme, keseimbangan cairan dan elektrolit. Pasien gagal ginjal kronis dapat dilakukan salah satu terapi pengganti fungsi ginjal untuk mempertahankan hidupnya yaitu hemodialisa. Pasien hemodialisa memiliki masalah defisit perawatan diri yang berdampak terhadap aktivitas sehari-hari akibat komplikasi yang terjadi seperti, kelemahan, hipotensi, nyeri, kram dan lain-lain. Tujuan penelitian ini adalah untuk mengidentifikasi diri sehari-hari pasien hemodialisa di Murni Teguh Memorial Hospital. Jenis penelitian ini adalah penelitian deskriftif. Sampel penelitian ini adalah pasien hemodialisa yang terdiri dari 35 orang dengan tekhnik accidental sampling. Aktivitas sehari-hari dianalisis dengan uji deskrifitif frekuensi dengan hasil penelitian mayoritas responden memiliki jenis aktivitas manajemen nutrisi sedang sebanyak 13 orang (37.10%), aktivitas mobilisasi/pergerakan buruk sebanyak 13 orang (37.10%), aktivitas rumah sedang dan buruk sebanyak 13 orang (37.10%), aktivitas istirahat tidur baik sebanyak 14 orang (40%) dan aktivitas tanggung jawab terhadap pengobatan sedang sebanyak 17 orang (48.60%). Penelitian ini menunjukkan pasien hemodialisa mengalami gangguan perawatan diri sehari-hari. Diharapkan petugas kesehatan perlu mengembangkan program pelatihan perawat untuk memperhatikan dan memberikan intervensi kepada pasien yang mengalami gangguan aktivitas sehari-hari untuk dapat meningkatkan kemampuan pasien dalam melaksanakan aktivitas sehari-hari.